Impact of media richness and flow on e-learning technology acceptance - Liu, Su-Houn; Liao, Hsiu-Li; Pratt, Jean A. (Computers and education, 2009)
Advances in e-learning technologies parallels a general increase in sophistication by computer users. The use of just one theory or model, such as the technology acceptance model, is no longer sufficient to study the intended use of e-learning systems. Rather, a combination of theories must be integrated in order to fully capture the complexity of e-learners, who are both system users and learners. The current research presents an integrated theoretical framework to study users’ acceptance of streaming media for e-learning. Three streams of research provide the basis for this integrated framework: the technology acceptance model, flow theory and media richness theory. Students enrolled in an online section of an information systems course used one of three different combinations of text, streamed audio and streamed video. Regression analysis was used to test the hypotheses in this field experiment. Perceived ease of use was a predictor of perceived usefulness; both the perceived usefulness and the attitude of the user were predictors of intention to use. Richer content-presentation types were positively correlated with higher concentration levels but showed mixed results when correlated with perceived usefulness. Results from this study have practical implications for those interested in integrating streaming media into e-learning.